Minimal residual disease testing in hematologic malignancies and solid cancer. (July 2014) - Ben Lassoued, Amin; Nivaggioni, Vanessa; Gabert, Jean
<x xml:space="preserve">Abstract</x> Minimal residual disease (MRD) assays are of a great value to assess treatment efficacy and may provide prognostic information. This is particularly relevant in the era of targeted therapy where the introduction of MRD monitoring has fundamentally transformed the way in which cancer patients are managed. While MRD guidelines are well-established for chronic myeloid leukemia, acute promyelocytic leukemia and acute lymphoblastic leukemia, areas for continuing development are available. High level of standardization and regular external quality control rounds and recommendations for data interpretation remain essential to improve MRD monitoring. In this review, we describe the different applications of MRD assays in most frequent hematologic malignancies and solid cancer and provide an overview of the strengths and potential weaknesses of each method.